Modeling the Inactivation of Intestinal Pathogenic Escherichia coli O157:H7 and Uropathogenic E. coli in Ground Chicken by High Pressure Processing and Thymol - Chien, Shih-Yung; Sheen, Shiowshuh; Sommers, Christopher H.; Sheen, Lee-Yan (Frontiers in Microbiology, 2016)
Disease causing Escherichia coli commonly found in meat and poultry include intestinal pathogenic E. coli (iPEC) as well as extraintestinal types such as the Uropathogenic E. coli (UPEC). In this study we compared the resistance of iPEC (O157:H7) to UPEC in chicken meat using High Pressure Processing (HPP) in with (the hurdle concept) and without thymol essential oil as a sensitizer. UPEC was found slightly more resistant than E. coli O157:H7 (iPEC O157:H7) at 450MPa and 500 MPa. A central composite experimental design was used to evaluate the effect of pressure (300-400 MPa), thymol concentration (100-200 ppm), and pressure-holding time (10-20 min) on the inactivation of iPEC O157:H7 and UPEC in ground chicken. The hurdle approach reduced the high pressure levels and thymol doses imposed on the food matrices and potentially decreased food quality damaged after treatment. The quadratic equations were developed to predict the impact (lethality) on iPEC O157:H7 (R2 = 0.94) and UPEC (R2 = 0.98), as well as dimensionless nonlinear models [Pr > F (< 0.0001)]. Both linear and non-linear models were validated with data obtained from separated experiment points. All models may predict the inactivation/lethality within the same order of accuracy. However, the dimensionless nonlinear models showed potential applications with parameters outside the central composite design ranges. The results provide useful information of both iPEC O157:H7 and UPEC in regard to how they may survive HPP in the presence or absence of thymol. The models may further assist regulatory agencies and food industry to assess the potential risk of iPEC O157:H7 and UPEC in ground chicken.